Strategi Guru dalam Mengintegrasikan Lingkungan Tempat Tinggal Sebagai Sumber Pembelajaran IPS Kelas Rendah di Sekolah Dasar Negeri 017108 Sentang - Aulia Atirka; Ayunda Nurfika Zahra; Rizky Ananda Putri Dalimunthe; Widyaratnasari; Zulham Siregar (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to describe teachers' strategies in integrating the home environment as a learning resource for Social Studies (IPS) in lower grades at SD Negeri 017108 Sentang. The study used a qualitative approach with a descriptive type. The research subjects included the principal, lower grade teachers, and students. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results showed that the main strategies of teachers were carried out through utilizing the home environment as a learning context, linking IPS material with students' daily experiences, giving environmental observation assignments, and applying varied learning methods. These strategies created a more contextual learning and encouraged students' active involvement in observing, discussing, and connecting IPS concepts with real conditions in their surroundings. The successful implementation of the strategy was supported by the diverse potential of the environment, school support, student enthusiasm, and parental involvement, while the main obstacles included limited time, weather conditions, differences in student characteristics, and limited learning media. Teachers overcame these obstacles by adjusting strategies, utilizing alternative media, and providing learning assistance according to students' needs. This study confirms that the integration of the residential environment as a learning resource is a pedagogical strategy that supports contextual and meaningful social studies learning in lower elementary school grades.